PERUBAHAN STRUKTUR EKONOMI INDONESIA - Emi Suwarni (Jurnal Ekonomi Pembangunan, 2006)
This research is conducted to indentify the changes of Indonesian economic structural., period of 1996 to 2005. The data used in this research obtan from central board of statistics. The results show that Indonesian economics structural based on the gross domestic product (GDP) by primary sector, secondary sector and tertier sector from 1996 to 2005 has been change. Contribution of primary sector to GDP has been decreased from 31 percent in 1996 to 23 percent in 2005. Contribution of secondary sector has been increased from 34,83 percent in 1996 to 35,37 percent in 2005. Mean while, contribution of tertier sector has also been increased from 37,88 percent to 40,80 percent in 2005. This finding is relevant with chenery theory. The chenery theory mention that the changes of economic structural will be in line with economic change process. KeywordS: Structural changes, primary sector, secondary sector, tertier sector.